Effect of Class-Wide Peer Tutoring on Senior Secondary School Students’ Achievement in Chemistry - Nwafor, Stephen Chinedu; Ezeanya, Maureen Chinyere; Onuigwe, Blessing Ukamaka (Papanda Publisher, 2024)
There is an urgent need to improve students’ achievement in Chemistry in Nigeria using innovative teaching methods due to the available empirical evidence. This study therefore examined the effect of CWPT (class-wide peer tutoring) on the academic achievement of chemistry students in Anambra State, Nigeria. Additionally, it looked into the moderating effect of gender on students' chemistry achievement as well as the interplay between gender and instructional tactics. Data was gathered from 78 Senior Secondary two (SS2) Chemistry students using a 30 multiple-choice items Chemistry achievement test created by researchers. The Kendall's Coefficient of Concordance (w) was used to get the reliability index for CAT, which was 0.92. Pre-test and post-test non-equivalent control group quasi-experimental design was the methodology utilized in the study. Mean and standard deviation were used to respond to the study questions, and ANCOVA was used to assess the hypotheses. The findings of the investigation showed that CWPT improves students' achievement in chemistry more than the lecture technique does. Additionally, neither gender nor the interaction between gender and instructional strategies had a statistically significant impact on students' achievement in chemistry. It was concluded that CWPT promotes gender equity in chemistry learning and Improves students’ achievement in Chemistry.